Characterization, Pathogenicity And Chemical Control Of Colletotrichum Spp. Associated With Chilli (Capsicum Annuum And C. Frutescens) Anthracnose In Peninsular Malaysia - Noor, Nuraini Mohd (2017)
Anthracnose fruit rot caused by Colletotrichum spp. is a serious post-harvest disease causing losses of chilli in Peninsular Malaysia. For identification of the causal pathogen, many studies were only based on morphological characteristics which are not sufficient as many Colletotrichum spp. belongs to a species complex. Molecular characterization based on a single gene is also not sufficient especially to differentiate closely related species. Correct identification of Colletotrichum spp. associated with anthracnose is important to strategize suitable disease control methods and for quarantine purposes. In this study, morphological and molecular characteristics as well as pathogenicity of Colletotrichum isolates from chilli anthracnose were evaluated.